Opening the black box of the common-law legal regime: Contrasts in the development of corporate law in Britain and the United States in the late nineteenth and early twentieth centuries. Issue 7 (3rd October 2019) - Harris, Ron; Lamoreaux, Naomi R.
ABSTRACT: The general incorporation laws enacted in Britain and the US in the nineteenth century had strikingly different structures. Whereas British law was laissez-faire in spirit, the American statutes were highly regulatory. The literature on the efficiency of the common law might lead one to expect that these statutory differences would become less salient over time, as businesses litigated their disputes and courts in the two countries came to similar resolutions. However, the authors find that the case law tended, if anything, to accentuate the differences in the statutes. British courts typically enforced whatever arrangements shareholders wrote into their articles of association or otherwise contracted among themselves, so long as the agreements were not contrary to law. In the US, by contrast, courts generally refused to enforce shareholders' agreements that deviated in any significant way from statutory norms. US law would not really begin to converge on British law until the second half of the twentieth century, when states began to enact more flexible general incorporation statutes. By that time, British company law was also becoming more regulatory.